Experimental analysis of passive bandwidth estimation tool for multiple hop wireless networks - Nurul Amirah, Abdullah (2013)
The crucial problem in the wireless network mesh was the available bandwidth.Available bandwidth is the highest throughput that the path can provide to certain consideration. There two techniques used to measure the available bandwidthswhich were passive and active measurement. Passive measurement allowed the network to be measure without alters the network traffic. This research willrepresent an experimental analysis of available bandwidth by using passive bandwidth estimation tool. The passive bandwidth estimation tools that were used were Pathload, Pathrate and Wbest. The objective of the research was to measure the available bandwidth using passive bandwidth estimation tool, compare the selected tools based on their estimation preference and to recommend the best bandwidth estimation tools. This was determined with the three factors which were the failure pattern, accuracy and consistency of the tools. The experimental analysis was done in two scenarios which were in the optimum network and network with traffic. For each scenario, the testing then was done in three different environments, one router, two routers with same bandwidth and two routers with higher bandwidth at the bridging. Laptop was placed between an access points. Twenty reading for each tool then was recorded. At the end of the experiment, the data then was analyzed to determine the result based on the objective of the experiment. Based on the result, Pathrate was the best tools to be used for both environment followed by Pathload and Wbest.